Biofuels from perennial energy crops on buffer strips: A win-win strategy. (15th May 2021) - Agostini, A.; Serra, P.; Giuntoli, J.; Martani, E.; Ferrarini, A.; Amaducci, S.
Abstract: The objective of this work was to assess the environmental performances of advanced biofuels produced from perennial energy crops (miscanthus and willow) grown in bioenergy buffer strips (BBS) and compare them with the environmental performances of alternative systems providing the same function, i.e. private mobility. The growing evidence of potentially negative environmental impacts of bioenergy pathways calls for renewed efforts in identifying win-win bioenergy pathways, thus capable of mitigating climate change without worsening other environmental impacts. An holistic approach encompassing all the relevant areas of environmental concern is thus fundamental to highlight environmental trade-offs. Therefore, in this study we follow an attributional Life Cycle Assessment approach, but our analysis includes detailed modelling of biogenic carbon pools, nutrients cycles, infrastructures' impacts as well as the expansion of the system boundaries to include the fuel use. We find that the fragmented and linear configuration of the buffer strips does not affect significantly the GHG emissions of lignocellulosic ethanol for BBS compared to growing the crops in open field. Additionally, we find that ethanol from perennials grown in BBS has the potential to reduce several other environmental impacts associated to private mobility. Firstly, the cultivation of miscanthus and willow in BBS enables both the removal of nutrients from the environment and the removal of carbon from the atmosphere, through the creation of an additional terrestrial sink. Secondly, when compared to the use of fossil gasoline, bioethanol from BBS crops generates lower impacts on all other areas of environmental concern, such as resources depletion or air pollution. We also find that cars fuelled with bioethanol form buffer strips perform even better than electric vehicles in all the impact categories analysed except for acidification and particulate matter emissions, where battery electric vehicles running on renewables perform slightly better. We conclude that bioethanol from perennial crops grown in BBS is a good example of nature-based solution, able to reduce GHG emissions without shifting the environmental burden on other areas of environmental concern. Graphical abstract: Image 1 Highlights: A comprehensive approach to the assessment of the environmental impact is fundamental. Bioethanol from miscanthus and willow has negative GHG emissions. Perennial energy crops in bioenergy buffer strips (BBS) reduce eutrophication. Bioethanol from perennial energy crops in BBS is a win-win option.